2022
DOI: 10.1021/acsanm.2c01941
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nanowires with Increasing Aspect Ratios for Room-Temperature NO2 Gas Sensing

Abstract: The oriented design and controllable preparation of sensing materials are extremely important and meaningful attributes that not only contribute to the realization of desirable gas-sensing properties but also facilitate the validation of the sensing mechanism. Because of the spatial effect derived from micelle assemblies formed by surfactant molecules under certain circumstances, radial growth of ZnO crystals is successfully suppressed in this work, which leads to the formation of ZnO nanowires with a larger a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…It has been found that wide-bandgap nanoparticles are highly sensitive and efficient gas-sensing materials. Although the surfaces of bulk materials are almost entirely depleted of carriers, nanomaterials demonstrate a greater change in conductance when exposed to gas than bulk-size grains because more carriers are activated at the surface from their trapped states to the conduction band [25][26][27][28][29]. Metal oxide nanoparticles' surface absorbs the molecules of a reducing gas, lowering the potential barrier by moving electrons into the conduction band and lowering electrical resistance [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that wide-bandgap nanoparticles are highly sensitive and efficient gas-sensing materials. Although the surfaces of bulk materials are almost entirely depleted of carriers, nanomaterials demonstrate a greater change in conductance when exposed to gas than bulk-size grains because more carriers are activated at the surface from their trapped states to the conduction band [25][26][27][28][29]. Metal oxide nanoparticles' surface absorbs the molecules of a reducing gas, lowering the potential barrier by moving electrons into the conduction band and lowering electrical resistance [30][31][32].…”
Section: Introductionmentioning
confidence: 99%